Adverse events of high-dose tigecycline in the treatment of ventilator-associated pneumonia due to multidrug-resistant pathogens. Issue 38 (September 2018) - Chen, Zihan; Shi, Xiaoyan
Abstract : Abstract: The off-label uses of tigecycline (TGC) to treat ventilator-associated pneumonia (VAP) have aroused worldwide concerns. The efficacy about TGC has been recently reported. However, the adverse events (AEs) remain controversial. Our study aims to analyze the safety of the high-dose (HD) regimens in the treatment of VAP due to multidrug-resistant (MDR) pathogens. The clinical data of 134 patients who were diagnosed with VAP from January 2013 to December 2015 in the NeuroScience Care Unit (NCU) were analyzed retrospectively. The incidence and the occurrence time of AEs, 28-day mortality, and the factors of clinical effectiveness were explored. A total of 54 patients received the standard dose group (SD), 69 in the HD, and 11 in the nonstandard HD group (NHD). Acinetobacter baumannii were the main pathogenic bacteria. There was no statistic difference in the incidence of AEs and the 28-day mortality among the 3 groups ( P  > .05). Total bilirubin (TBIL) increased significantly after SD of TGC treatment ( P  = .004). Liver dysfunction occurred the latest (10.83 ± 7.08), not in the duration of HD group (9.63 ± 3.92), whereas in the SD group (13.00 ± 7.57) and NHD group (12.64 ± 3.70). Patients with septic shock, MODS, and higher APACHE II score were of high risk in mortality. The HD group was associated with higher clinical effective rate and bacteria clearance rate. HD TGC was relatively safe and tolerable in ICU patients. The risk of side effects was related to the TGC duration, although not increased as the dosage rose. Full course of the HD regimen was associated with better outcomes for the treatment of VAP patients, especially for the MDR gram-negative bacilli infection. Inappropriate antimicrobial treatment might lead to clinical treatment failure. Abstract : Supplemental Digital Content is available in the text